Health Experts’ Perspectives on Barriers, Facilitators, and Needs for Improvement of Hospital Care in the Dying Phase - Sukhvir Kaur; Kathleen Boström; Anneke Ullrich; Nikolas Oubaid; Karin Oechsle; Holger Schulz; Raymond Voltz; Kerstin Kremeike (International Journal of Clinical Practice)
Introduction. Globally, hospitals are an important place in end-of-life care and most frequent place of death in Germany (47%), but at the same time, the least preferred one—both for patients and their informal caregivers. As hospital care in the dying phase on non-palliative care wards has rarely been studied systematically, we assessed the current state of care in the dying phase in hospitals as a first step. Methods. In an online survey, N = 165 national health experts were invited to answer eight open questions on care aspects, facilitators, barriers, and needs for improvement as well as COVID-19 pandemic specifics regarding hospital care in the dying phase. Sociodemographic data were analysed descriptively, and responses were analysed using qualitative thematic analysis. Results. Of n = 65 experts, 52% work as nursing staff and 30% as physicians. We identified facilitators, barriers, and needs for improvement regarding 11 topics on the following three levels: institutional level (general institutional conditions, hospital culture, and integration of specialist palliative care), team level (attitude towards and dealing with death and dying, competencies, communication, and teamwork) and care level (dying phase, symptom control, patient centredness, and involvement of informal caregivers). Conclusion. Improving care in the dying phase has to overcome barriers on various levels. We assume that rather “small” measures will find their way into clinical routine and contribute to the improvement of hospital care in the dying phase.